ANALISIS ZAKAT PRODUKTIF BAZNAS KOTA MEDAN DALAM PENGEMBANGAN USAHA MIKRO KECIL MENENGAH ( UMKM) MUSTAHIK DI KECAMATAN MEDAN TIMUR KOTA MEDAN - Hilman Hidayat; Erliyanti; Dewi Sundari Tanjung (HIBRUL ULAMA, 2025)
his study aims to determine the influence of productive zakat distribution ($X_1$) on the empowerment of mustahik ($Y$). This research employs a quantitative approach, with data collected through questionnaires and observation methods. Data analysis techniques include quantitative descriptive analysis, normality testing, t-tests, and multiple linear regression analysis. Based on the research findings and discussions presented in the previous chapters, it can be concluded that the significance value in the partial t-test is 0.00, which is smaller than 0.05 ($0.00 < 0.05$), and the t-statistic is greater than the ttable ($14.803 > 2.003$). These results indicate that, partially, the distribution of productive zakat has a positive and significant influence on the welfare of mustahik at BAZNAS Medan City. Therefore, the research hypothesis ($H_a$) is accepted. Furthermore, the R-Square value is 0.793, meaning that the independent variable (productive zakat) can explain 79.3% of the variance in the dependent variable (mustahik welfare). Thus, it is confirmed that the distribution of productive zakat has a significant and positive effect on the welfare of mustahik at BAZNAS Medan City